The European discovery of America - Morison, Samuel Eliot, 1887-1976 (Oxford University Press, 1993)
The late Samuel Eliot Morison, a former U.S. Navy admiral, was also one of America's premier historians. Combining a first-hand knowledge of the sea and transatlantic travel with a brilliantly readable narrative style, "The European Discovery of America" has become nothing less than the definitive account of the great age of European exploration. -- From publisher's description.